Analysis of Learning Resources Biology Book by Neil A. Campbell for class X SMA / Equivalent - Liza Choirun Nisa; Juniarti Wulan Lestari; Prayitno Ribut Suwasono; Slamet Slamet; Yovita Besi (International Journal of Sustainable English Language, Education, and Science, 2026)
This study aims to determine the results of content analysis in the Biology book by Neil A. Campbell for class X SMA / equivalent using Science Literacy. This research method is descriptive qualitative with the research subject is the Biology book by Neil A. Campbell for class X SMA / equivalent. The research instrument is a book suitability analysis. Data collection is based on the results of the analysis conducted by researchers on Biology by Neil A. Campbell for class X SMA / equivalent based on science literacy content. Based on the analysis, the suitability of the Biology book by Neil A. Campbell for grade X SMA / equivalent seen from science literacy is categorized in the Science book as a body of knowledge (a body of knowledge).